Kastélyépítészet és kastélykultúra Magyarországon : a historizmus kora = [Country house-building and country house culture in Hungary : the age og historicism] - Sisa, József (Vince Kiadó, 2007)
Summary: 357- 366 : Country house-building and country house culture in Hungary : the age og historicism